2014
DOI: 10.1002/chem.201402229
|View full text |Cite
|
Sign up to set email alerts
|

CNN Pincer Ruthenium Catalysts for Hydrogenation and Transfer Hydrogenation of Ketones: Experimental and Computational Studies

Abstract: Reaction of [RuCl(CNN)(dppb)] (1-Cl) (HCNN=2-aminomethyl-6-(4-methylphenyl)pyridine; dppb=Ph2 P(CH2 )4 PPh2 ) with NaOCH2 CF3 leads to the amine-alkoxide [Ru(CNN)(OCH2 CF3 )(dppb)] (1-OCH2 CF3 ), whose neutron diffraction study reveals a short RuO⋅⋅⋅HN bond length. Treatment of 1-Cl with NaOEt and EtOH affords the alkoxide [Ru(CNN)(OEt)(dppb)]⋅(EtOH)n (1-OEt⋅n EtOH), which equilibrates with the hydride [RuH(CNN)(dppb)] (1-H) and acetaldehyde. Compound 1-OEt⋅n EtOH reacts reversibly with H2 leading to 1-H and E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 149 publications
4
44
0
1
Order By: Relevance
“…Density functional theory (DFT) calculations carried out on model complexes RuX(CNN)(dmpb) (X = H, OR) (HCNN = 2-aminomethyl-6-(phenyl)pyridine, dmpb = Me 2 P(CH 2 ) 4 PMe 2 ) in the presence of added molecule of 2-propanol showed that the reaction of the Ru hydride with the ketone substrate leads to the most stable Ru alkoxide, the species observed in solution by NMR [54].…”
Section: H MLmentioning
confidence: 98%
See 4 more Smart Citations
“…Density functional theory (DFT) calculations carried out on model complexes RuX(CNN)(dmpb) (X = H, OR) (HCNN = 2-aminomethyl-6-(phenyl)pyridine, dmpb = Me 2 P(CH 2 ) 4 PMe 2 ) in the presence of added molecule of 2-propanol showed that the reaction of the Ru hydride with the ketone substrate leads to the most stable Ru alkoxide, the species observed in solution by NMR [54].…”
Section: H MLmentioning
confidence: 98%
“…EtOH is kept under H 2 (5 atm), the hydride 38a, which is present in trace, starts to form through hydrogen splitting, affording a mixture 38a/123 in 2:3 ratio. Catalytic investigations on the HY of acetophenone with 36a in ethanol show that high activity is observed in a defined "pH window" [54]. As a matter of fact, under acidic conditions the Ru-H would be protonated resulting in H 2 formation, whereas in basic conditions the presence of a large amount of alkoxide may prevent H 2 coordination to the Ru center.…”
Section: Mechanistic Studies On Hydrogen Transfer and Hydrogenation Mmentioning
confidence: 99%
See 3 more Smart Citations